Seurantatutkimus tyytyväisyydestä suoriutumisen arviointiin suomalaisissa yliopistoissa vuosina 2010–2020 - Kallio, Tomi J.; Lehtivuori, Aki; Kallio, Kirsi-Mari (Hallinnon tutkimuksen seura, 2025)
In this study, based on a broad empirical 10-year follow-up dataset, the satisfaction of respondents from three Finnish universities, representing four different disciplines, is examined in relation to the performance evaluations implemented by university administrations. Based on empirical analysis, the study presents two key observations, which the article attempts to further understand in light of theory and extant literature. Firstly, there is clear dissatisfaction among the respondents regarding the performance evaluations carried out by their university administrations. This observation is in line with findings reported in previous literature, which conveys a similarly critical tone regarding performance measurement and management practices in universities. Secondly, the empirical analysis suggests that the aforementioned dissatisfaction appears to diminish at a statistically significant level over the 10-year follow-up period of the study. This finding is significant, as previous research literature has not reported similar results.